The Fat-1 Transgene in Mice Increases Antioxidant Potential, Reduces Pro-Inflammatory Cytokine Levels, and Enhances PPARγ and SIRT-1 Expression on a Calorie Restricted Diet. Issue 5 (2009) - Rahman, Md Mizanur; Halade, Ganesh V.; Bhattacharya, Arunabh; Fernandes, Gabriel
Abstract : Both n-3 fatty acids (FA) and calorie-restriction (CR) are known to exert anti-inflammatory and anti-oxidative effects in animals and humans. In this study, we investigated the synergistic anti-inflammatory and anti-oxidative capacity of n-3 FA and CR using Fat-1 transgenic mice (Fat-1) that are capable of converting n-6 FA to n-3 FA endogenously. Wild type (WT) and Fat-1 mice were maintained on ad libitum (AL) or CR (40% less than AL) AIN-93 diet supplemented with 10% corn oil (rich in n-6 FA) for 5 months. Significantly lower levels of n-6/n-3 FA ratio were observed in serum, muscle and liver of Fat-1 mice fed AL or CR as compared to that of WT mice fed AL or CR. Muscle catalase (CAT), super oxide dismutase (SOD), glutathione peroxidase (GPX) activities, and liver CAT and SOD activities were found higher in Fat-1 mice as compared to that of WT mice. These activities were more pronounced in Fat-1/CR group as compared to other groups. Serum pro-inflammatory markers, such as tumor necrosis factor (TNF)α, interleukin (IL)-1β and IL-6 were found lower in Fat-1 mice, as compared to that of WT mice. This anti-inflammatory effect was also more pronounced in Fat-1/CR group as compared to that of other groups. Furthermore, significantly higher levels of peroxisome proliferator-activated receptor (PPA R)gamma and life prolonging gene, sirtuin (SIRT)-1 expression were found in liver of Fat-1/CR mice, as compared to that of WT/CR mice. These data suggest that n-3 FA along with moderate CR may prolong lifespan by attenuating inflammation and oxidative stress.